Animal Welfare Issues Associated with Rearing Dairy Calves in Nepalese Context - Sah, Nirvay (Journal of applied animal ethics research, 2022)
Abstract In Nepal, a predominantly Hindu country, most communities consider the cow as a sacred animal leading to their special place in society. However, male calves are neglected because of their limited utility in the context of religiously restricted beef consumption. A cross-sectional survey was conducted among the dairy farmers of the Chitwan district in the central region of Nepal to understand the rearing practices of dairy calves and the associated animal welfare concerns. A majority of the producers (70%) that participated in the survey reared female calves to be replacement dairy animals, hence providing better care and management on the farm. Male calves, however, were vulnerable to indiscriminate removal following non-humane methods; 20% of calves starved by feed withdrawal, and 20% of calves chased away from the farm to live as stray animals. Therefore, the religious, sentimental, economic, and ethical analysis of the welfare situation needs to be assessed in a broader context and a sustainable policy needs to be implemented to change the overall attitude of the farmers towards male dairy calves.